2021
DOI: 10.3390/lubricants9050057
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Twin for Friction Prediction in Dynamic Rubber Applications with Surface Textures

Abstract: Surface texturing is an effective method to reduce friction without the need to change materials. In this study, surface textures were transferred to rubber samples in the form of dimples, using a novel laser surface texturing (LST)—based texturing during moulding (TDM) production process, developed within the European Project MouldTex. The rubber samples were used to experimentally determine texture-induced friction variations, although, due to the complexity of manufacturing, only a limited amount was availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The development of a holistic design software has already been started at ITAINNOVA and preliminary results have been obtained. The software, based on ROM results for different rubber materials, geometries, operating conditions, and textures, is proven to be a powerful tool to compute real-time predictions for both friction and DF values 4 , 48 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of a holistic design software has already been started at ITAINNOVA and preliminary results have been obtained. The software, based on ROM results for different rubber materials, geometries, operating conditions, and textures, is proven to be a powerful tool to compute real-time predictions for both friction and DF values 4 , 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The DoE was planned (see Table 7 ) with a statistical software 49 ; a 2-level full factorial design including 3 factors and 1 center point with 3 replicates was selected. Values of DDD were selected according to finite element analysis (FEA) simulations 48 , where friction reduction of textured rubber seals in dynamic conditions was expected and finally achieved. We found that the texturing of the metal plates increased the DF, which could compromise the correct texture transfer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon a LHS (70 data sets) and contact simulations, the contact pressure, lubricant film height, and frictional force were predicted with CoPs larger than 82%, allowing subsequent optimization with an EA. Zambrano et al [117] used reduced order modeling (ROM) to predict and optimize the frictional behavior of surface textures in dynamic rubber applications under different operating conditions. It is noteworthy that this was based on a limited number of experimental measurements and the ROM was fed with microscope-based texture measurements.…”
Section: Surface Texturingmentioning
confidence: 99%
“…Surface texturing is an effective way to achieve these goals without changing the material or lubricant. Zambrano et al combined friction measurements of a surface textured rubber specimen with Reduced Order Modelling to compute optimal surface texture parameters that provide the highest friction reduction within a given parameter space [23]. One class of materials that comes into focus here are thiol-acrylate polymers, which exhibit excellent shape memory behaviour upon thermal triggering [24,25].…”
Section: Introductionmentioning
confidence: 99%